1999
DOI: 10.1002/(sici)1097-4547(19991201)58:5<624::aid-jnr3>3.3.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of the PMP22 gene in glioma and osteogenic sarcoma cell lines

Abstract: Previously we reported the amplification of the peripheral myelin protein 22 (PMP22) gene in cell lines of human osteogenic and glioma tumors. PMP22 normally is expressed at high levels in Schwann cells of the peripheral nervous system and is suggested to function as a structural protein of the myelin sheath. One of the most common inherited peripheral neuropathies, Charcot-Marie-Tooth Type 1A (CMT1A), is associated with a duplication of a 1.5-Mb DNA region on chromosome 17p11.2 - p12 containing PMP22. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Most research on PMP22 proteins has focused on the nervous system. However, recent several studies show that PMP22 regulates tumor development, metastasis, and invasion in different cancers [8][9][10][11][12][13][14][15][16][17][18][19]21]. At present, there is no clear evidence of PMP22 acting as an oncogene or as a tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most research on PMP22 proteins has focused on the nervous system. However, recent several studies show that PMP22 regulates tumor development, metastasis, and invasion in different cancers [8][9][10][11][12][13][14][15][16][17][18][19]21]. At present, there is no clear evidence of PMP22 acting as an oncogene or as a tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 99%
“…International Publisher that PMP22 is a potential tumor suppressor [8][9][10][11][12][13], whereas some observations suggest a potential oncogenic function of PMP22 [14][15][16][17][18][19][20][21][22]. Few studies have examined the function and regulation of PMP22 in gastric cancer.…”
Section: Ivyspringmentioning
confidence: 99%
“…PMP22 participates in the oncogenesis, progression, and metastasis of osteosarcoma (23)(24)(25)(26). Furthermore, high-level PMP22 amplification was observed in high-grade glioma (27,28). In the current study, we revealed for the first time the role of PMP22 in gastric cancer in potentially mediating selfrenewal and chemoresistance in gastric cancer cells.…”
Section: Discussionmentioning
confidence: 57%
“…The precise expression and function of PMP22 in tumors remain to be clarified. Several studies indicate that PMP22 is a potential tumor suppressor (21,22), whereas some observations suggest a potential oncogenic function of PMP22 in tumors (23)(24)(25)(26)(27)(28). Studies on the role of PMP22 in regulating gastric cancer have not been reported, and we describe here that PMP22 is required for both self-renewal and chemoresistance in gastric cancer.…”
Section: Introductionmentioning
confidence: 68%
“…Amplification of the PMP22 expression has been identified in glioma and osteosarcoma cell lines. 12,13 Nevertheless, no preclinical or clinical data about the role of the PMP22 in ependymal cells exists. Therefore, no link between ependymoma and PMP22 gene can be drawn or speculated.…”
Section: Discussionmentioning
confidence: 99%